Avaliação da função diastólica do ventrículo esquerdo na miocardiopatia chagásica em três etapas de tratamento da insuficiência cardíaca: convencional, otimizada e associada ao emprego de carvedilol - Braulio Muzzi Ribeiro de Oliveira (2009)
Chronic Chagas cardiomyopathy causes substantial morbidity andmortality in Latin America and its prognosis is dependent on systolic anddiastolic left ventriclar (LV) function. Whether renin-angiotensin system(RAS) inhibitors and beta-blockers are safe and beneficial in this group ofpatients has been challenged because of the lack of formal trials.Objective: The objective of this study was to determine the efficacy ofrenin-angiotensin system (RAS) inhibitors and beta-blockers in improvingdiastolic dysfunction in chronic Chagas cardiomyopathy.Methods: We conducted a double-blind, placebo-controlled, andrandomized trial in 41 patients with Trypanosoma cruzi infection andcardiomyopathy. All patients received enalapril (up-titrated to 20 mg BID)and spironolactone (25 mg QD). Subsequently, the patients were randomly assigned to receive placebo (n=20) or carvedilol up-titrated to 25 mg BID (n=19). The end points were changes in LV diastolic function parameters evaluated by transthoracic Doppler echocardiography after RAS inhibition and that after the addition of carvedilol, and change in brain natriuretic peptide (BNP) levels, used as a surrogate marker of LV filling pressure. Results: Optimization of RAS inhibition was safe and associated with improvement in LV diastolic function parameters: isovolumic relaxation time (137.47 ms vs. 151.55 ms, p=0.02), increase of inferior wall E velocity (6.55 cm/s vs. 7.30 cm/s, p=0.03), decrease of inferior E/E index (9.23 vs. 8.36, p=0.065), and increase of antero-lateral wall A (6.05 vs. 6.78, p=0.02). BNP levels decreased significantly [95.90 vs 32.55; p=0.026]. Treatment with carvedilol was associated with a trend toward a preservation of diastolic parameters: decrease in systolic pulmonary venous flow index (0.52 vs. 0.48, p=0.029), and a decrease in inferolateral wall E velocity in placebo group (6.55 cm/s vs. 7.30 cm/s, p=0.03), both not observed in the carvedilol group. LV flow propagation velocity decreased in the first stage of treatment and increased after carvedilol association (24.31cm/s vs. 30.60 cm/s, p=0.004). There was no significant change in BNP levels [86.95 (123.05) vs. 31.40 (184.38); p=0.525]. Conclusions: In patients with chronic Chagas cardiomyopathy,optimizatin of treatment with enalapril and spironolactone was associated with significant benefits in LV diastolic cardiac function and a decrease of BNP levels, and subsequent addition of carvedilol was associated with a trend toward a prevention of worsening of diastolic dysfunction, without changes in BNP levels. Key Words: diastolic function, heart failure, Chagas cardiomyopathy, brain natriuretic peptide, echocardiography